The impact of Twitter and Facebook on the political culture of university professors in eight metropolises of Iran - mehdi bigdeloo (مطالعات رسانه‌های نوین, 2018)
Political culture in Iran as a cultural space that manifests the way people relate to the political system has affected in recent decades various phenomena such as revolution, the structure of the political system, government agents, and so on. In this cultural context, the phenomenon of virtual social networking has left many works in recent years. But the phenomenon, and in particular the Twitter and Facebook networks, have been able to affect the political culture of university professors as other historical phenomena as the most exploitative of these two social networks, the issue that the present study aims to answer to a case-to-face approach And at the descriptive-analytical level. This study, using the views of the humanities professors of the universities of eight metropolitan areas of the country in a survey method, and then analyzing the data obtained using the Tao Kendall test, concluded that three functions of development of regulatory capabilities, convergence of social communication and the valuation of Twitter and Facebook The sum of the six components of the eight components of the political culture of political users in Iran has been effective, including all three functions of the critique of the political system; two functions affecting distrust, alienation, and the superiority of religious values and only one function on extremism and self-rule, and extra-judicial behaviors Intellectual absolutism also does not affect these functions.